Attracting Early‐Stage Investors: Evidence from a Randomized Field Experiment - BERNSTEIN, SHAI; KORTEWEG, ARTHUR; LAWS, KEVIN (Journal of Finance, 2017)
ABSTRACT This paper uses a randomized field experiment to identify which start‐up characteristics are most important to investors in early‐stage firms. The experiment randomizes investors’ information sets of fund‐raising start‐ups. The average investor responds strongly to information about the founding team, but not to firm traction or existing lead investors. We provide evidence that the team is not merely a signal of quality, and that investing based on team information is a rational strategy. Together, our results indicate that information about human assets is causally important for the funding of early‐stage firms and hence for entrepreneurial success.